Research of youth gender differences in tobacco consumption in Turkey - Alkan, Ömer (Journal of Dependence, 2017)
Objective: Tobacco habits are one of the major public health problems that are becoming increasingly common among our young people. The purpose of this study is to determine the frequency of tobacco use among male and female aged 15-25 in Turkey and the risk factors that may have an impact on tobacco use. Method: The study is a descriptive and causal-comparative study. From the Turkish Health Survey questionnaire, cross-sectional data of 3568 male and 4218 female subjects aged 15-25 years were used. Frequency analyzes of tobacco use by young male and female were given, and chi-square independence tests were conducted to determine whether there is a relationship between tobacco use and variables in the questionnaire. All variables were considered together, and two categories of logistic regression analysis were used to determine the risk factors affecting tobacco use in male and female. Results: 79.3% of male and 87.1% of female who smoke live in urban. The frequency of alcohol use among male and female who smoke was 27.5% and 20.8%, respectively. Male who graduated from university have a higher tendency to smoke than those with the lowest education level (Odds Ratio: 2,86, %95 confidence intervel: 1,71-4,79). Male (Odds Ratio: 5,07, %95 confidence intervel: 3,26-7,88) and female (Odds Ratio: 16,19, %95 confidence inter-vel: 9,62-27,25) exposed to tobacco more than 5 hours a day at home are more likely to smoke than those who are never exposed. Conclusion: The results of the study show that the effects of risk factors associated with tobacco use are greater in male than in female. Policies to prevent tobacco use need to be given more importance to young people who are exposed to tobacco at home, who use alcohol, and who have a high monthly income.